Дом. Замок из песка - Знаменская А. (АСТ : Астрель : Полиграфиздат, 2012)
Экземпляры: б/ф №2 (20161021) / Инвентарный номер: 36217 / Цена: 84.00 / Авт.знак: З-72 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6